Kajian Kapasitas Saluran Pada Sistem Jaringan Drainase Untuk Mengatasi Genangan Pada Wilayah Telkom Dan Pasar Buah (Jalan Sudirman Pekanbaru) - Fahrul Iswar; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
This study analyzed drainage capacity, conducting drainage flow patterns that affect the Sago River, to cope with floodwaters in the area of the intersection of Jalan Sudirman-Jalan Hang Tuah (Office Telkom) and Pasar Buah, Pekanbaru, and calculate the flow rate when the rainfall intensity high. The data required in this study conducted in two ways, namely field surveys and institutional surveys. Hydrological analysis was conducted to determine the intensity of the rain, in the form of daily rainfall data for 15 years (1997-2011). From the analysis of the plan obtained daily rainfall (R24) for the 5-year anniversary when the study area is 126.798 mm. Tackle the problem at the point of flooding Pasar Buah can be done by adding dimension to channel SD SG KR2 with added height channel (H) between 5-50 cm. Tackle the problem of flooding at the point of Telkom can be done by adding dimension to channel SD SG KR5 with added height channel (H) between 15-50 cm and channel SG AS KR1 with added height channel (H) between 15-50 cm. Keywords: drainage, flow pattern, flow, flood